TG13 guidelines for diagnosis and severity grading of acute cholangitis (with videos) - Kiriyama, Seiki; Takada, Tadahiro; Strasberg, Steven M.; Solomkin, Joseph S.; Mayumi, Toshihiko; Pitt, Henry A.; Gouma, Dirk J.; Garden, O. James; Büchler, Markus W.; Yokoe, Masamichi; Kimura, Yasutoshi; Tsuyuguchi, Toshio; et al. (Journal of hepato-biliary pancreatic sciences, 2013)
Since the publication of the Tokyo Guidelines for the management of acute cholangitis and cholecystitis (TG07), diagnostic criteria and severity assessment criteria for acute cholangitis have been presented and extensively used as the primary standard all over the world. However, it has been found that there are crucial limitations in these criteria. The diagnostic criteria of TG07 do not have enough sensitivity and specificity, and its severity assessment criteria are unsuitable for clinical use. A working team for the revision of TG07 was organized in June, 2010, and these criteria have been updated through clinical implementation and its assessment by means of multi-center analysis. The diagnostic criteria of acute cholangitis have been revised as criteria to establish the diagnosis where cholestasis and inflammation demonstrated by clinical signs or blood test in addition to biliary manifestations demonstrated by imaging are present. The diagnostic criteria of the updated Tokyo Guidelines (TG13) have high sensitivity (87.6 %) and high specificity (77.7 %). TG13 has better diagnostic capacity than TG07. Severity assessment is classified as follows: Grade III: associated with organ failure; Grade II: early biliary drainage should be conducted; Grade1: others. As for the severity assessment criteria of TG07, separating Grade II and Grade I at the time of diagnosis was impossible, so they were unsuitable for clinical practice. Therefore, the severity assessment criteria of TG13 have been revised so as not to lose the timing of biliary drainage or treatment for etiology. Based on evidence, five predictive factors for poor prognosis in acute cholangitis—hyperbilirubinemia, high fever, leukocytosis, elderly patient and hypoalbuminemia—have been extracted. Grade II can be diagnosed if two of these five factors are present.
TG13: Updated Tokyo Guidelines for acute cholangitisand acute cholecystitis
Gesehen am 22.06.2022